2016
DOI: 10.1016/j.jchf.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin-2 and Soluble Flt1 Levels in Peripartum Cardiomyopathy

Abstract: Background Peripartum cardiomyopathy (PPCM) is an uncommon disorder with unknown etiology. Angiogenic imbalance may contribute to its pathophysiology. We explore the association of vascular hormones with myocardial recovery and clinical outcomes in PPCM. Methods and Results In 98 women with newly diagnosed PPCM enrolled in the Investigation in Pregnancy Associated Cardiomyopathy (IPAC) study, serum was obtained at baseline for analysis of relaxin-2, prolactin, soluble fms-like tyrosine kinase 1 (sFlt1), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 33 publications
(41 reference statements)
1
43
1
2
Order By: Relevance
“…In the IPAC cohort, the vasodilatory and pro-angiogenic hormone relaxin was associated with less left ventricular dilatation at diagnosis and earlier recovery of left ventricular function 64. In addition, an increase in troponin concentration is modestly associated with persistent left ventricular dysfunction.…”
Section: Natural Course and Prognosismentioning
confidence: 90%
See 2 more Smart Citations
“…In the IPAC cohort, the vasodilatory and pro-angiogenic hormone relaxin was associated with less left ventricular dilatation at diagnosis and earlier recovery of left ventricular function 64. In addition, an increase in troponin concentration is modestly associated with persistent left ventricular dysfunction.…”
Section: Natural Course and Prognosismentioning
confidence: 90%
“…SFlt-1 levels decline rapidly after delivery (after the placental source of sFlt-1 is removed) in healthy women but remain higher than the normal range in women with PPCM 6264. The source of persistently raised sFlt-1 postpartum is not currently known.…”
Section: Pathogenesis and Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…These factors are diverse from being clinical, hormonal, or imaging modalities. Some examples include race, comorbidities, relaxin level, pro‐BNP titer, LV dimension in diastole, and global longitudinal strain 1, 2, 3, 4, 5. A consensus on how to estimate the risk of PPCM relapse is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…It has a variety of haemodynamic effects, including increased cardiac output and decreased systemic vascular resistance, as well as anti-inflammatory and antifibrotic properties. Higher levels of relaxin-2 are associated with increased rates of myocardial recovery 16. A recent trial of relaxin in acute heart failure (not in PPCM) reported no reduction in cardiovascular death or worsening heart failure 17.…”
Section: What Causes Ppcm?mentioning
confidence: 99%